2017
DOI: 10.1103/physrevlett.118.158005
|View full text |Cite
|
Sign up to set email alerts
|

Screening, Hyperuniformity, and Instability in the Sedimentation of Irregular Objects

Abstract: We study the overdamped sedimentation of non-Brownian objects of irregular shape using fluctuating hydrodynamics. The anisotropic response of the objects to flow, caused by their tendency to align with gravity, directly suppresses concentration and velocity fluctuations. This allows the suspension to avoid the anomalous fluctuations predicted for suspensions of symmetric spheroids. The suppression of concentration fluctuations leads to a correlated, hyperuniform structure. For certain object shapes, the anisot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(83 citation statements)
references
References 46 publications
11
72
0
Order By: Relevance
“…Long-range hydrodynamic correlations among settling particles in a viscous liquid lead to complex many-body dynamics, exhibiting very large density fluctuations and large-scale dynamic structures when the particles are spheres or other centrally symmetric objects [338][339][340][341]. Goldfriend, Diamant and Witten studied [342] the over damped sedimentation of non-Brownian objects of irregular shape using fluctuating hydrodynamics. They showed that the anisotropic response of the objects to flow, caused by their tendency to align with gravity, directly suppresses density and velocity fluctuations in certain directions with varying intensities.…”
Section: Statistical Anisotropic Structuresmentioning
confidence: 99%
“…Long-range hydrodynamic correlations among settling particles in a viscous liquid lead to complex many-body dynamics, exhibiting very large density fluctuations and large-scale dynamic structures when the particles are spheres or other centrally symmetric objects [338][339][340][341]. Goldfriend, Diamant and Witten studied [342] the over damped sedimentation of non-Brownian objects of irregular shape using fluctuating hydrodynamics. They showed that the anisotropic response of the objects to flow, caused by their tendency to align with gravity, directly suppresses density and velocity fluctuations in certain directions with varying intensities.…”
Section: Statistical Anisotropic Structuresmentioning
confidence: 99%
“…All structurally perfect crystals and quasicrystals are hyperuniform, but typical disordered many-particle systems, including gases, liquids, and glasses, are not. Disordered hyperuniform many-particle systems are exotic states of amorphous matter that have attracted considerable recent attention [10,47,4,55,12,54,24,23,50,30,27,14,21,46]. (1.6)].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies of very large systems that explicitly identify a crossover length ξ ρ below which the system is uniform [39] suggest that ξ ρ might increase somewhat in the dual limit as the pressure is decreased towards the jamming transition and the equilibration time increases [39]. Density hyperuniformity has also been predicted for sedimentation [40] and periodically sheared suspensions [41,42].…”
mentioning
confidence: 99%